Output impedance improvement of a Low Voltage Low Power Current mirror based on body driven technique. (October 2016) - Bastan, Yasin; Hamzehil, Elahe; Amiri, Parviz
Abstract: This paper improved the output impedance of a Low Voltage Low Power (LVLP) current mirror by using body driven technique and transconductance enhancement. The applied technique increases the output impedance of current mirror significantly compared to other works. Also, it provides 0.5 Ω and 6 MHz improvement in input resistance and bandwidth, respectively. Operation principle of current mirror circuit with proposed improvement is discussed, the most important formulas are derived and the comparison between the performance of this circuit and the primary one is verified by simulation in TSMC 0.18 µm CMOS technology. An output resistance of 39.5 GΩ is achieved for the improved circuit that shows 5 GΩ increment in comparison with primary circuit. Besides, simulation results show an input resistance of 12.8 Ω and −3 dB cut-off frequency of 216 MHz for the improved current mirror circuit while it consumes only 42.5 µW. Also, other specifications still remain unchanged. It should be noted that in this simulation, the power supply is 1 V and the input current is 15 µA.